Geometrical design of minichannels with rectangular wall cavities for flow boiling heat transfer enhancement - Mohammad Sina Yaghoubi; Ali Ahmadpour; Majid Saffar-Avval (Results in Engineering)
Implementing wall cavities inside minichannels has been suggested as a promising technique for flow boiling heat transfer enhancement. Still, few studies have focused on the effect of geometrical parameters of the cavities on the overall thermo-hydraulic performance of the two-phase flow field. In the present study, the flow boiling inside a minichannel with wall cavities is numerically simulated using the OpenFOAM flow solver, and a parametric study is carried out to find optimal geometrical measures of wall cavities for the first time. The problem is unsteady, and the fluid properties are considered constant. The governing equations are discretized using the finite volume method on a three-dimensional structured grid. The Lee mass transfer model and volume of fluid (VOF) are adopted to model the liquid-to-vapor phase change phenomenon. The impact of cavity depth and pitch on the local and average heat transfer coefficients, vapor phase distribution, and temperature field are examined, and the thermohydraulic performance of textured wall minichannel is quantified using a proper performance index. Up to a six-fold increase in heat transfer coefficient is achieved using the rectangular side wall cavities compared to the plain channel. Moreover, the result showed an optimal design point for the problem with non-dimensionalized depth and pitch of cavities equal to 3 and 5, respectively, for which a performance index as large as 2.25 is reported.